The relationship between firefighters’ physical performance characteristics and simulated firefighting demands - McKayla Schmit; Mark DeBeliso (Turkish Journal of Kinesiology, 2019)
Prior research indicates firefighting to be a demanding and hazardous profession that places tremendous amounts of stress on the body, both physically and mentally. Likewise, degraded fitness levels can affect the firefighter’s (FF) ability to execute rescue tasks efficiently and places the imperiled and FF at risk for injury or death. The current study examined the relationship between physical fitness tests (PFT) and Simulated Fire Ground Test (SFGT) performance among active FF.  Twenty (n=20) male career FF (age 37.8±8.4 years, height 182.1±7.0 cm, body mass 95.6±8.9 kg) were assessed for PFT and the SFGT. The PFT assessments included: maximum grip strength (GS), 3-minute step test, vertical jump (VJ), 1-RM back squat (BS), and 1-RM bench press (BP). The SFGT was composed of: stair climb with hose bundle (SC), 30m charged hose advance (CHA), and 30m dummy drag (DD). The SFGT demands were completed in full PPE (personal protective equipment) gear and pack. SFGT scores were then compared to the PFT scores with Pearson correlation coefficients (r). Grip strength demonstrated a negative moderate (r=-0.49: p<0.05) relationship with the time to complete the CHA, a high negative relationship with the SC times (r=-0.61: p<0.05), a high negative relationship with the DD times (r=-0.70: p<0.05), and a high negative relationship the total time to complete all tasks (r=-0.64: p<0.05). Heart rate response, measured as %HRmax following the step test demonstrated a positive moderate relationship with the time to complete the SC (r=0.51: p<0.05), CHA (r=0.52: p<0.05), and the total time to complete all tasks (r=0.50: p<0.05); and a positive low (r=0.38: p<0.05) relationship with the time to complete the DD. The BP 1-RM demonstrated a negative high relationship with the time to complete the SC (r=-0.79: p<0.05) and CHA (r=-0.79: p<0.05); and a negative very high relationship with the time to complete the DD (r=-0.80: p<0.05) and the total time to complete all tasks (r=-0.82: p<0.05). The SQ 1-RM demonstrated a negative moderate (r=-0.52: p<0.05) relationship with the time to complete the CHA; and a negative high relationship with the time to complete the SC (r=-0.70: p<0.05), DD (r=-0.68: p<0.05), and the total time to complete all tasks (r=-0.70: p<0.05) (p<0.05). The VJ scores demonstrated a negative moderate (r=-0.49: p<0.05) relationship with the time to complete the CHA; and a negative high relationship with the time to complete the SC (r=-0.67: p<0.05), DD (r=-0.60: p<0.05), and the total time to complete all tasks (r=-0.66: p<0.05). Peak power relative to body mass demonstrated a negative moderate relationship with the time to complete the SC (r=-0.55: p<0.05), DD (r=-0.42: p<0.05), and the total time to complete all tasks (r=-0.52: p<0.05); and a negative low non-significant relationship with the time to complete the CHA (r=-0.30: p>0.05). Age did not demonstrate a significant relationship with performance on any of the SGFT assessments (p>0.05). Within the parameters of this study, FF’s exhibited a moderate to very high relationship between PFT and the execution of simulated firefighting demands.